The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s12274-017-1838-2
|View full text |Cite
|
Sign up to set email alerts
|

Selective toxicity of hydroxyl-rich carbon nanodots for cancer research

Abstract: Authors are required to submit a graphic entry for the Table of Contents (TOC) in conjunction with the manuscript title. This graphic should capture the readers' attention and give readers a visual impression of the essence of the paper. Labels, formulae, or numbers within the graphic must be legible at publication size. Tables or spectra are not acceptable. Color graphics are highly encouraged. The resolution of the figure should be at least 600 dpi. The size should be at least 50 mm × 80 mm with a rectangula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 46 publications
(56 reference statements)
2
18
0
1
Order By: Relevance
“…The biocompatibility of carbon‐based nanoparticles is widely known as nontoxic, [ 17 ] and CNPs have demonstrated no toxic and/or inhibitory effects on the bacteria. [ 24 ] Corresponding to the previous reports, the bare CNPs prepared in this study also showed no activities against the bacteria assessed regardless of the synthetic routes. The results from the bacteria cells incubated with TC alone indicated very low inhibitory activities owing to the efficient efflux system (Figure 4e).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The biocompatibility of carbon‐based nanoparticles is widely known as nontoxic, [ 17 ] and CNPs have demonstrated no toxic and/or inhibitory effects on the bacteria. [ 24 ] Corresponding to the previous reports, the bare CNPs prepared in this study also showed no activities against the bacteria assessed regardless of the synthetic routes. The results from the bacteria cells incubated with TC alone indicated very low inhibitory activities owing to the efficient efflux system (Figure 4e).…”
Section: Discussionsupporting
confidence: 84%
“…No bacterial inhibitory activities were observed from either the CNP‐BUp or CNP‐TDn when tested alone on both Gram‐positive and Gram‐negative species, representative of the high degree of biocompatibility of the bare, unmodified CNPs ( Table 1 ; Tables S5 and S6, Supporting Information), and are consistent with a previous report on the antibacterial activities of CNPs of this type. [ 24 ] However, as presented in Table 1 and Figure 2 , K. pneumonia , A. baylyi , and P. vulgaris were inhibited strongly in comparison with P. aeruginosa and P. mirabilis . The lowest MIC (2 × 10 −6 m equivalent TC concentration ) was exhibited by the TC–CNP‐BUp conjugate against A. baylyi , whereas the MIC of TC alone in this cell line was 21 × 10 −6 m , an approximate tenfold potentiation in activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…16 As for the production methods, Kim et al observed differences in mortality of A. franciscana stage I nauplii exposed for 24 and 48 h to carbon nanodots produced by the same synthetic method and precursors, but using different solvents. 44 Considering that, in our study, GO induced slight, but significant, mortality only in A. franciscana adults, only the organisms at this developmental stage were investigated for their susceptibility to GO, evaluating other biomarkers and parameters of toxicity. One of the main mechanisms of GBM toxicity appears to be an increased ROS production and consequent oxidative stress, as previously demonstrated in human cells exposed to GO.…”
Section: Discussionmentioning
confidence: 96%
“…The carbon core structure is necessary for bioimaging, the effects of light-emitting diodes, mass spectrometry, and thermal therapy, whilst the nature of functional groups at the surface is responsible for enzyme and gene regulation effects, electro- and organo-catalysis, and drug delivery applications [ 48 , 49 , 50 ]. As photoluminescence is essential for bioimaging and biosensing applications, to date, enormous efforts are being made with the following final goal: To precisely define factors that enable the accurate and reproducible synthesis of materials with optimal photoluminescence properties [ 31 , 48 ].…”
Section: General Properties Of Carbon Nanomaterialsmentioning
confidence: 99%